Atenolol in the atopic child with infantile hemangioma. - Bonifazi, E.; Milano, A. (European Journal of Pediatric Dermatology, 2018)
Infantile emagioma responds to propranolol as well as corticosteroids but side effects are much less important; however, there are also side effects with propranolol and among these the most often leading to suspend propranolol is the bronchospasm favored by blocking of beta-2 receptors. At therapeutic doses for hemangioma, atenolol does not have this side effect because it is a selective beta-blocker and acts only on beta-1 receptors. Since bronchial hyperreactivity is more common in atopic children, in the current prospective study we divided the children who needed beta-blockers for their hemangioma into two groups: the first group of 20 children with atopic relatives of 1st degree was treated with atenolol, the second group consisting of 17 children with negative for atopy family history was treated with propranolol. The efficacy of the therapy and the incidence of side effects was not different between the 2 groups. However, the group with atenolol despite the atopic familiarity underwent fewer episodes of bronchospasm of the group with propranolol. Atenolol, which is already considered a second-choice beta-blocker in the case of side effects of propranolol, may become the first-choice beta-blocker in special subgroups of children with hemangiomas, such as those with a biparental atopic family history.